A TWO CENTURY RECORD OF STRONTIUM ISOTOPES FROM AN ICE CORE DRILLED AT MT BLANC, FRANCE - Burton G.R.; Rosman K.J.R.; Van de Velde K.P.; Boutron C.F. (My University, 2006)
New techniques which allow small amounts of Sr to be reliably analysed [G.R. Burton, V.I. Morgan, C.F. Boutron, K.J.R. Rosman, High-sensitivity measurements of strontium isotopes in polar ice, Anal. Chim. Acta 469 (2002) 225-233] by TIMS (Thermal Ionisation Mass Spectrometry) have been used to measure the isotopic composition of Sr and the concentration of Rb and Sr at sub-nanogram per gram levels in a Mt Blanc snow and ice core. This two century time series of Sr isotopes is the first to be reported in an Alpine glacier. The Sr and Rb concentrations range from 3 ng/g to 20 pg/g and 1 ng/g to 10 pg/g, respectively, with higher concentrations evident in more recent times. This trend is consistent with that reported previously for other metals such as Cd, Cu and Zn [K. Van de Velde, C. Barbante, G. Cozzi, I. Moret, T. Bellomi, C. Ferrari, C. Boutron, Changes in the occurrence of silver, gold, platinum, palladium and rhodium in Mont Blanc ice and snow since the 18th century, Atmos. Environ. 34 (2000) 3117-3127; K. Van de Velde, C. Boutron, C. Ferrari, T. Bellomi, C. Barbante, S. Rudnev, M. Bolshov, Seasonal variations of heavy metals in the 1960s Alpine ice: sources versus meteorological factors, Earth Planet. Sci. Lett. 164 (1998) 521-533; K.J.R. Rosman, C. Ly, K. Van de Velde, C.F. Boutron, A two century record of lead isotopes in high altitude Alpine snow and ice, Earth Planet. Sci. Lett. 176 (2000) 413-424]. The 87Sr/86Sr ratios vary between 0.7020 and 0.7176 and display relatively larger variations in recent times which have been attributed to seasonal variations made evident by the increased sampling resolution available at shallower depths. No change with time is evident in this ratio which has a mean value of ~ 0.712 and is similar to Glacial ice at Summit Greenland, suggesting that aerosols reaching Mt Blanc represent the same mixture of sources. Also, anthropogenic sources would appear to have the same isotopic ratio. The presence of Saharan dust in some samples is confirmed here by their strontium isotopic ratios. © 2006 Elsevier B.V. All rights reserved.
Keywords: ICE CORES; ISOTOPES; ISOTOPIC TRACERS; LEAD; POLLUTION; STRONTIUM